Portable ultrasound: the next generation arrives - Ault, Mark J. (Springer Milan, 2010)
PURPOSE: A new category of handheld devices has recently emerged that are even smaller than current portable models, with their main advantages being increased portability and affordability relative to their counterparts. However, these new devices have not yet been thoroughly evaluated in the clinical setting. METHODS: A prospective, non-blinded, three-phase study was designed to evaluate a handheld ultrasound device as compared to a common compact ultrasound machine for the performance of paracenteses and thoracenteses on human patients. RESULTS: For the vast majority of straight-forward evaluations, the handheld device was sufficient to safely complete the procedure without further imaging. For difficult cases with smaller fluid collections or anatomic aberrations, further localization with the common compact machine continued to be useful to improve the operator’s confidence in the findings. CONCLUSION: This novice handheld device represents only one of what appears to be a growing number of new ultra-portable ultrasound devices on the market. These devices represent a new and exciting form of ultrasound technology that may benefit patients and physicians in multiple venues. While they are unlikely to replace standard ultrasound devices for many of the more complex applications, their extreme portability allows for ultrasound imaging in more diverse situations that has previously been practical. Based on our limited experience, the image quality is adequate and the learning curve is reasonable. Future integration of PDA technology could further the utility of these devices and additional study will be important to further define their appropriate niche and clinical utility.